Studi Kasus Tentang Penggunaan Make Up dan Analisis Sosial - Psikologis pada Siswa SMAN 15 Pekanbaru. (A Case Study on the Use of Make-Up and a Socio-Psychological Analysis among Students of SMAN 15 Pekanbaru) - Donal Donal; Dwi Rahmadani Indra; Tesa Sessio Mentiana; Aura Anisa Simarmata; Enjelika Aristi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study discusses the phenomenon of make-up use among adolescents, particularly female students at SMAN 15 Pekanbaru, which has become part of their lifestyle and a form of self-expression. The purpose of this research is to analyze the social and psychological factors influencing make-up use and its impact on students’ self-confidence and social adjustment. The method used is a case study with a qualitative approach through literature analysis and assessment of a student who regularly uses make-up. The results show that this behavior is influenced by family, peers, and social media, where make-up serves to enhance self-confidence but may also lead to dependency on social validation. Through individual counseling and psychoeducation, students are guided to build healthy self-confidence based on their personal potential rather than physical appearance. This study highlights the important roles of guidance and counseling teachers, parents, and schools in supporting students to channel their interest in make-up in a positive and balanced way.